New and revised groundwater snails (Mollusca, Caenogastropoda, Cochliopidae) from karst and associated hyporheic habitats in western Texas and northern Mexico - Kathryn E. Perez; Vanessa Saenz; Yamileth Guerrero; Lisa Gonzalez; Evan Guerrero; Pete Diaz; Benjamin T. Hutchins; Benjamin F. Schwartz (Subterranean Biology)
The freshwater gastropod family Cochliopidae is a diverse component of the subterranean fauna in the karst and hyporheic habitats of western Texas and northern Mexico, with 11 genera and 27 described species found in the region. Building on previous phylogenetic studies of the family in the region we incorporate additional sampling, DNA, and morphological study for systematic revision of species found in the western Edwards-Trinity Aquifer System and associated karst and hyporheic habitats. We describe three new species, Stygopyrgus variabilis sp. nov., Stygopyrgus gracilis sp. nov., and Phreatodrobia embossa sp. nov. and revise the generic placement of two others, Texapyrgus diaboli comb. nov. and Balconorbis coronae comb. nov.